NEW EMPIRICAL APPROACH WITH REGULARIZATION OF SCATTERED WELL LIQUID LEVEL DATA FOR INTERPRETABLE DOWNHOLE PRESSURE - Irianto, Nurdi
An idea to reduce operation cost due to oil price drop issues for well BHP buildup survey and well liquid level monitoring is by applying Acoustic Well Sounder (AWS). This method is the way to avoid rig cost and mechanical downhole operation. The technology applied in this research is by measuring well BHP from surface using mechanical wave interface. The wave investigates the depth of liquid surface in the well column. Each of the fluids in the column of the well has different properties and volume. The total fluids column represents well pressure profile and production capacity of the well. Some specific information is required for this indirect pressure prediction in well, includes the well pressure gradient, production rate, fluid phase in well, and fluid composition. This research establishes a prediction method of well bottom pressure value from scattered reading of liquid level by echo survey. The scope limitation is employed because the well is shallow with low production rate and low gas-oil ratio (GOR). In this research the well model is vertical pipe as of Poettman and Carpenter’s (1952) model, rather than Bexendell (1958) model while it works in well with high production rate. The AWS reading of BHP buildup and liquid level in the oil well contains noises due to some physical and mechanical condition. For example, the presence of foam will change sonic velocity. An idea to handle large scattered field data contains noises is by applying Tikhonov regularization. Liquid level survey is set up under shunt in well condition to clearly monitoring liquid level rising in the well column. The field data reading is then acquired. Because the liquid level data field reading using echosounder tool is scattered, the regularization recalculated of liquid level depth should be examined for noises factor in the field data. The equation is generated, and an initial condition of started liquid column height h0 and surface well production rate Q0 at t=0 is definite. The Volterra integral equation of the first kind is built for calculation purpose. An ill-posed problem performs in the data needs the solution. Tikhonov regularization has handling this problem. Optimum value of regularization parameter is employed to the calculation for fitness target solution. This research is an innovative idea for utilization of liquid level data monitoring in the well, while the acquired data is scattered or contains error. After the best appropriate regularized liquid level recalculation, the smoothness of the data as qualified model solution curve is fully advantageous for BHP buildup recalculation and interpretation. The study is in the shallow well with low rate of liquid production and limited gas will neglect the pressure traverse calculation. An expectation, that the well BHP buildup recalculation from regularized liquid level reading in well, can be as a substitution for well BHP buildup data while downhole pressure gauge survey is costly higher.